Local atomic and electronic structure in the LiVPO4(F, O) tavorite‐type materials from solid‐state NMR combined with DFT calculations. (1st July 2020) - Bamine, Tahya; Boivin, Edouard; Masquelier, Christian; Croguennec, Laurence; Salager, Elodie; Carlier, Dany
Abstract: 7 Li, 31 P, and 19 F solid‐state nuclear magnetic resonance (NMR) spectroscopy was used to investigate the local arrangement of oxygen and fluorine in LiVPO4 F1‐y Oy materials, interesting as positive electrode materials for Li‐ion batteries. From the evolution of the 1D spectra versus y, 2D 7 Li radiofrequency‐driven recoupling (RFDR) experiments combined, and a tentative signal assignment based on density functional theory (DFT) calculations, it appears that F and O are not randomly dispersed on the bridging X position between two X–VO4 –X octahedra (X = O or F) but tend to segregate at a local scale. Using DFT calculations, we analyzed the impact of the different local environments on the local electronic structure. Depending on the nature of the VO4 X2 environments, vanadium ions are either in the +III or in the +IV oxidation state and can exhibit different distributions of their unpaired electron(s) on the d orbitals. Based on those different local electronic structures and on the computed Fermi contact shifts, we discuss the impact on the spin transfer mechanism on adjacent nuclei and propose tentative signal assignments. The O/F clustering tendency is discussed in relation with the formation of short V IV O vanadyl bonds with a very specific electronic structure and possible cooperative effect along the chain. Abstract : 7 Li, 31 P, and 19 F MAS NMR study of LiVPO4 F1‐y Oy materials, interesting as positive electrode materials for Li‐ion batteries combined with DFT calculations, was used to investigate the local arrangement of oxygen and fluorine in those materials: it appears that F and O tend to segregate, probably due to the cooperative formation of vanadyl V IV O bonds along the chains.